Exploring the link between social axioms and perceived academic control - David, Adonis P. (Quezon City Psychological Association of the Philippines, 2012)
"This study explored the possible link between five dimensions of social axioms and perceived academic control. Tentative hypotheses were made on the basis of the argument that social axioms that define more personal control over life outcomes will positively predict perceived academic control."
Keywords: Social axioms; Religiosity; Perceived academic control; Personal control